Pengaruh Harga Dan Variasi Produk Terhadap Pembelian Ulang Kembali Dengan Mediasi Kepuasan Konsumen - Putra, Adi Jaya; Nur'Aeni (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
During the Covid-19 pandemic, people need food that is nutritious and healthy and can be stored for a long time, such as healthy instant noodles Supermi Nutrimi, instant noodles made with vegetables and rich in vitamins. The aim of this research is to examine the effect of repeat purchases on price, product variety and consumer satisfaction with Supermi Nutrimi healthy instant noodles. This research was conducted within the boundaries of the Bekasi Regency community area with a total of 105 respondents, namely consumers who consumed Supermi Nutrimi. The sampling technique used was nonprobability sampling, namely the purposive sampling method. This research tests correlation and regression with the help of SmartPLS 3.0 software which is used to test validity and reliability. This research shows that 1) The price set by Supermi Nutrimi has a positive but not significant effect on repeat purchases. 2) The variety of products offered by Supermi Nutrimi has a positive but not significant effect on repeat purchases. 3) The satisfaction felt by consumers has a positive and significant effect on repeat purchases. 4) Prices mediated by consumer satisfaction can have a positive and significant effect on repeat purchases. 5) Product variations mediated by consumer satisfaction can have a positive but not significant effect on repeat purchases.